Determining the preeminent plastic wastes in the production of petrol using pyrolysis method and its effectiveness as an alternative fuel - Herrero, Nelson Jun; Azañon, Rosenda; Alvaro, Abbie Jane; Ocampo, Darrel (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2024)
Abstract: This study aimed to determine which type of plastic – PET, HDPE, LDPE, PP, PS, and Others, produces most oil yield in terms of time of complete degradation, temperature and amount of plastics using a non-catalytic slow pyrolysis method; it also determined the physical characteristics of the oil yield in terms of its color and appearance; and it also aimed to determine which petroleum produced by different types of plastics are more efficient in terms of (a) production of oil and (b) combustion time. Production of oil and oil yield is presented in milliliters and percentage, respectively. Combustion time is expressed in seconds from the time of ignition to total disappearance of flame having 1ml of oil tested from each produced pyrolytic oil. Experimental-descriptive comparative method was used in determining the type of plastic that yields to most of pyrolytic oil. Based from gathered results, at constant temperature and amount of plastics, PS produced most petroleum at 29.5% oil yield followed by PP with 29%. While PET produced the least petroleum with 0.01% oil yield. Color varies at different types of plastics, given that PET and PP produces light brown color, LDPE produces light yellow while HDPE, PS and Others produces black color. PET, HDPE, PP, PS and Others produced liquefied petroleum while LDPE produces flammable wax product. PS produced most petroleum with 295ml (29.5%), and PET produced least oil with 1ml (0.01%). Combustion time varies at different types of plastics: PS at 145 seconds, PP at 141 seconds, HDPE at 115 seconds, Others at 78 seconds, LDPE at 77 seconds while PET produced non – flammable oil yield. Thus, PS is most efficient as an alternative fuel in terms of production and combustion time. For the betterment of similar study, future researchers are encouraged to test the pyrolytic oil yielded from different types of plastics in engine performance and machineries and the comparative performance to the available commercial fuels.